2020
DOI: 10.4103/jpbs.jpbs_115_20
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study to evaluate candidal parameters in the oral cavity of patients with type 2 diabetes mellitus

Abstract: A BSTRACT Aim: The aim of this study was to evaluate candidal parameters in the oral cavity of patients with type 2 diabetes mellitus (DM). Materials and Methods: The samples included in the study were divided into two groups: group A, comprises 50 patients with type 2 DM, and group B, comprises 30 subjects who were nondiabetic. A nonrandom consecutive sampling technique was used to enroll the subjects for the study. The χ2 test was used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…A statistically significantly strong association was seen between salivary glucose levels and candidal counts (P < 0.001) in the same. Vijayalakshm i, L et al, 2020 8…”
Section: Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…A statistically significantly strong association was seen between salivary glucose levels and candidal counts (P < 0.001) in the same. Vijayalakshm i, L et al, 2020 8…”
Section: Indiamentioning
confidence: 99%
“…Vijayalakshmi, L et al (2020) 8 showed diabetic individuals are prone to a hyperglycemic state, which in turn favors the growth and establishment of Candida species. Although a smaller percentage of multidrug-resistant Candida species has been observed in the saliva of patients with type 2 DM, it is prudent to consider prophylactic measures in such patients.…”
Section: Indiamentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Complete search strategies for each database and grey literature; Table S2: Excluded studies and reason for exclusion (n = 47); Table S3: Quality assessment of the individual included studies (n = 12) using The Joanna Briggs Institute Critical Appraisal Checklist for Cross-sectional Studies. References [ 3 , 5 , 8 , 11 , 17 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ] are cited in the supplementary materials .…”
mentioning
confidence: 99%